Perancangan Interior Restoran & Kafe Dengan Konsep Kontemporer Tradisional Khas Lombok di Lombok - David Pratama; Lintu Tulistyantoro; Hendy Mulyono (Intra, 2019)
This design is motivated by the problem that there is a lack of interest in the community, especially young people to preserve and maintain the culture that exists in Lombok. As time goes by, the culture that exists if not preserved, it will disappear over time. This restaurant and cafe offers a “wonderfull of songket house” design concept that will be based on Lombok culture, namely songket cloth and traditional house in lombok, with a more modern “contemporary” look to attract young childrens and tourists who come visiting Lombok to stop by there restaurant and cafe to presrve the culture in Lombok, and to be able to introduce to the culture to the tourists on the island of Lombok.